2014
DOI: 10.3126/ijasbt.v2i4.11047
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of an Enhanced Oil Recovery process with various chemicals for Naharkatiya Oil Field

Abstract: This paper reports the effect of using black liquor whose main constituent is Na- lignosulfonate, which is the effluent from Nagaon paper Mill, Jagiroad, Assam, along with Alkali and Co-surfactant in enhanced crude oil recovery from Upper Assam porous media. In this paper an attempt has been done to study the change in Inter Facial Tension (IFT) with different concentration of Surfactant and also a comparative study has been done determine the change in IFT with or without Alkali and Co-Surfactant. Increasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…Most matured or underperforming reservoirs of Upper Assam Basin are under chemical EOR (Gogoi 2011(Gogoi , 2014a. Already slugs comprising of anionic surfactant/ surfactants/alkali EOR flooding were attempted in most reservoirs of Upper Assam Basin (Phukan et al 2018;Hazarika and Gogoi 2014). These slugs reduce IFT between the aqueous and oleic phases which in turn increase the capillary number to overcome the capillary forces increasing the microscopic displacement efficiency of the reservoir.…”
Section: Introductionmentioning
confidence: 99%
“…Most matured or underperforming reservoirs of Upper Assam Basin are under chemical EOR (Gogoi 2011(Gogoi , 2014a. Already slugs comprising of anionic surfactant/ surfactants/alkali EOR flooding were attempted in most reservoirs of Upper Assam Basin (Phukan et al 2018;Hazarika and Gogoi 2014). These slugs reduce IFT between the aqueous and oleic phases which in turn increase the capillary number to overcome the capillary forces increasing the microscopic displacement efficiency of the reservoir.…”
Section: Introductionmentioning
confidence: 99%
“…Das and Gogoi (2015a, b) also observed that surfactant in the form of micelar can reduce the IFT between the oleic and aqueous phase to 10 −3 mN/m, thus leading to the EOR (Das and Gogoi 2015a, b). Initial studies on SDS has done by Hazarika et al (2018), he worked on anionic surfactant for Upper Assam Basin, and SDS was found to be efficient (Hazarika et al 2018;Hazarika and Gogoi 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the replacement of fossil‐based products with biomass‐based products has been actively investigated . In particular, lignocellulosic materials are considered to be promising feedstocks since they are plentiful, inexpensive and renewable …”
Section: Introductionmentioning
confidence: 99%
“…Lignin is one of the main components of biomass . Lignin has primarily been used as a fuel source, but recent studies have shown that it could be converted into several value‐added products . Using lignin as a feedstock for producing value‐added products has some advantages and disadvantages.…”
Section: Introductionmentioning
confidence: 99%